2021
DOI: 10.21037/tcr-21-994
|View full text |Cite
|
Sign up to set email alerts
|

MiRNA-339 targets and regulates ZNF689 to inhibit the proliferation and invasion of gastric cancer cells

Abstract: Background: Gastric cancer (GC) is the most common malignant tumor of the digestive system, and its mortality rate ranks first among malignant tumors. However, the pathogenesis of GC has not yet been fully elucidated. This study found that microRNA (miRNA)-339 is abnormally expressed in GC tissues. However, the role and molecular mechanism of miRNA-339 in the occurrence and development of GC are still unclear. Methods: Fluorescence quantitative polymerase chain reaction (qPCR) was used to detect the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As a cancer biomarker, miRNA was also closely related to various aspects of normal physiology and pathology, such as the occurrence, proliferation, differentiation, and apoptosis of lung cancer cells. In recent years, miRNA has attracted social research attention ( Jiang et al, 2021 ; Zhang et al, 2022 ). Gou et al (2020) found that inhibition of cardiomyocyte-derived Exo-miR-19a-3p promoted angiogenesis and improved cardiac function in mice with myocardial infarction by targeting HIF-1 α .…”
Section: Discussionmentioning
confidence: 99%
“…As a cancer biomarker, miRNA was also closely related to various aspects of normal physiology and pathology, such as the occurrence, proliferation, differentiation, and apoptosis of lung cancer cells. In recent years, miRNA has attracted social research attention ( Jiang et al, 2021 ; Zhang et al, 2022 ). Gou et al (2020) found that inhibition of cardiomyocyte-derived Exo-miR-19a-3p promoted angiogenesis and improved cardiac function in mice with myocardial infarction by targeting HIF-1 α .…”
Section: Discussionmentioning
confidence: 99%